Effects of SGLT2 inhibitors on cardiovascular death and all-cause death in patients with type 2 diabetes and chronic kidney disease: an updated meta-analysis including the SCORED trial. (September 2021) - Zhao, Li-Min; Zhan, Ze-Lin; Qiu, Mei
Background: The effects of sodium-glucose transporter 2 (SGLT2) inhibitors on cardiovascular death (CV death) and all-cause death (AC death) in patients with type 2 diabetes (T2D) and chronic kidney disease (CKD) are currently under intensive investigation. We intended to conduct an updated meta-analysis including the SCORED trial to evaluate the effects of SGLT2 inhibitors on death and cardiorenal events in this vulnerable population. Methods: Cardiorenal outcome trials of SGLT2 inhibitors were included. Primary outcomes were CV death and AC death, while secondary outcomes were hospitalization for heart failure (HHF), myocardial infarction (MI), CKD progression, cardiovascular death or hospitalization for heart failure (CV death or HHF), major adverse cardiovascular events (MACE), and stroke. Meta-analysis was conducted for each outcome. Results: Eight trials were included for meta-analysis. Compared with placebo, SGLT2 inhibitors significantly lowered the risk of CV death (HR = 0.86, 95% CI = 0.75–0.98), AC death (HR = 0.87, 95% CI = 0.79–0.96), HHF (HR = 0.64, 95% CI = 0.56–0.74), MI (HR = 0.76, 95% CI = 0.65–0.89), CKD progression (HR = 0.62, 95% CI = 0.54–0.72), and CV death or HHF (HR = 0.73, 95% CI = 0.67–0.80). No heterogeneity existed in the above meta-analyses (all I 2 values = 0%), whereas moderate heterogeneity existed in the meta-analyses for MACE and stroke (I 2 = 31.6% and 44.5%, respectively). Conclusions: Our findings suggest that SGLT2 inhibitors versus placebo significantly lower death, heart failure, renal failure, and MI events in patients with T2D and CKD. Head-to-head trials are needed to examine the possible differences in the effects of various gliflozins on MACE and stroke.